The effects of smart phone video analysis on focus of attention and performance in practice and competition. (March 2020) - Yeoman, Beth; Birch, Phil D.J.; Runswick, Oliver R.
Abstract: Objectives: Research has consistently found that focus of attention (FOA) affects motor learning and performance. However, much of the previous work has used artificially manipulated FOA of novice participants performing laboratory tasks. There is a paucity of work that has tested transfer to more complex competition environments. We aimed to investigate the effects of smart phone video analysis, which commonly occurs in natural practice settings in golf, on skilled player's FOA and performance in both practice and competition. Design: This study employed a mixed experimental design. The between participants factor was the use of video analysis (practice with video vs practice only) and the repeated measures factor was time point (pre-intervention vs post-intervention). Method: Altogether, 19 skilled golfers (handicap: M = 5.79, SD = 5.80) took part in a four-week practice intervention with ( n = 10) or without ( n = 9) the use of smart phone video analysis. Driving range performance and competition performance were measured pre- and post-intervention. Practice diaries provided measures of FOA during the intervention period. Results: The practice with video group displayed a significantly more internal FOA throughout the intervention period than the practice only group. This resulted in a significant time by group interaction for driving range performance that showed an increase in performance for the practice only group and a decrease for the practice with video group. However, the performance effects did not transfer to competition scores. Conclusions: Findings enhance our understanding of the effects of video analysis on FOA and question whether FOA effects transfer from on range practice to on course performance. Highlights: Smart phone video analysis created a more internal focus of attention during golf practice. Internal focus negatively affected performance in the practice environment (driving range). Performance effects observed in practice did not transfer to on course competition scores.